2018
DOI: 10.1093/icesjms/fsy015
|View full text |Cite
|
Sign up to set email alerts
|

Production, mortality, and infectivity of planktonic larval sea lice, Lepeophtheirus salmonis (Krøyer, 1837): current knowledge and implications for epidemiological modelling

Abstract: Current sea louse models attempt to estimate louse burdens on wild and cultured salmon by predicting the production and distribution of lice larvae and estimating the risk of transmission. While physical characteristics of water bodies and weather can be accurately modelled, many aspects of sea lice biology require further parameterization. The aims of this review are (i) to describe current knowledge regarding the production, mortality, and infectivity of planktonic sea lice larvae and (ii) to identify gaps i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 119 publications
0
69
0
Order By: Relevance
“…Additionally, the ability of water-borne pathogens to infect or infest a host can be influenced by the physical properties of the water they encounter, which can impact the growth, survival, and/or maturation of the pathogen (Brooker et al 2018). For example, viruses will eventually degrade under ultraviolet B exposure (Jacquet and Bratbak 2003); bacterial or fungal pathogens can become spores in unfavourable abiotic conditions, to become infectious later in conditions more suited to their survival (Lennon and Jones 2011); temperature can impact bacterial replication rates and temperature stress can make hosts more susceptible to bacterial infection (Holt et al 1989), and parasitic larvae development and survival rates are dependent on the water salinity and temperature they encounter (Groner et al 2016a;Samsing et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the ability of water-borne pathogens to infect or infest a host can be influenced by the physical properties of the water they encounter, which can impact the growth, survival, and/or maturation of the pathogen (Brooker et al 2018). For example, viruses will eventually degrade under ultraviolet B exposure (Jacquet and Bratbak 2003); bacterial or fungal pathogens can become spores in unfavourable abiotic conditions, to become infectious later in conditions more suited to their survival (Lennon and Jones 2011); temperature can impact bacterial replication rates and temperature stress can make hosts more susceptible to bacterial infection (Holt et al 1989), and parasitic larvae development and survival rates are dependent on the water salinity and temperature they encounter (Groner et al 2016a;Samsing et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, Groner et al's 2016 metaanalysis on salinity's impact on sea lice survival found a general trend of decreasing survival with decreasing salinity, with 20 psu resulting in larval death (Groner et al 2016a). The high fecundity and wide larval dispersal capabilities of the sea lice life cycle benefit their overall survival and success (Brooker et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Supply of Atlantic salmon has increased by 384% since 1995, with a world production of 2248 t in 2016 (FAO 2018); however, production growth in recent years has dropped by 7% (Marine Harvest 2017). The largest concern to the industry has been parasi tic sea lice, namely Lepeophtherius salmonis Krøyer and Caligus spp., estimated to cost the global industry £700 (~€ 950) million annually (Brooker et al 2018b). Widely used chemicals for the removal of lice, such as the orally administered emamectin benzoate, marketed as SLICE ® , and bath-administered hydrogen peroxide H 2 O 2 , are showing reduced efficacy (Jones et al 2013, Helgesen et al 2015, and in recent years attention has shifted to biological control using cleaner fish, in particular wrasse (Labridae spp.)…”
Section: Introductionmentioning
confidence: 99%
“…Demand for ballan wrasse is largely met by wild-caught fish, although farming of cleaner fish has developed in the last 5 yr, with the production of 118 000 wrasse in the UK in 2016 (Munro & Wallace 2017). Due to long generation times, wild-caught broodstock have been used exclusively in wrasse culture to date (Brooker et al 2018b), and as wrasse farming becomes more common, it is increasingly important to understand the health status of these wild populations which are either directly transferred for deployment on Scottish salmon farms or used as broodstock.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrates that UVC light has the potential to be an effective preventative lice treatment for the salmon farming industry by reducing the abundance of infective copepodid stages exported from farms. Atlantic salmon farms with relatively high numbers of adult female lice can produce an enormous quantity of larvae (150–965 eggs per eggstring:), and thus are likely to contribute the vast majority of copepodids in coastal waters around fish farms . Reducing export of copepodids from farms will result both in considerably lower infestation pressure for adjacent wild salmonid populations and lower farm re‐infestation rates following delousing treatments.…”
Section: Discussionmentioning
confidence: 99%